Salmonella enterica and Entamoeba histolytica co-infection presenting as multiple liver abscesses in an immunocompetent patient - Singh, Jaiveer; Panneerselvam, Rajapriyan; Sundaramurthi, Sudharsanan; Chellapa, Vijaykumar; Sathasivam, Sureshkumar (International Surgery Journal, 2025)
People living with the human immunodeficiency virus (PLHIV) are likelier to have Salmonella infections and bloodstream invasion than immunocompetent people. Here, we present a case with liver abscess due to co-infection Entamoeba histolytica and Salmonella enterica with no co-morbidities, immunocompromised states or any alcohol or other substance abuse history. A 36-year-old male with no significant co-morbidities presented with complaints of abdominal pain and fever. On examination, the right hypochondrium was tender without guarding or rigidity. Amoebic serology was positive. Stool culture isolated Salmonella group B and abscess culture revealed Salmonella enterica. HIV serology was negative. The ultrasound revealed hepatomegaly, two well-circumscribed abscesses in the liver, with right-sided pleural effusion. The patient was managed with ultrasound-guided pigtail drainage, followed by antibiotic therapy. Even though the co-infection of Salmonella and Entamoeba leads to abscess in immunocompetent individuals, which is rare, we should not overlook the possibility of the diagnosis.